(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Small and medium-sized enterprises are considered the backbone of the national economy. In addition to employment and social cohesion, innovation as a process of continuous development is often mentioned in connection with the contribution of SMEs to the national economy. The purpose of innovation is assurance of development, competitiveness and process and manufacturing effectiveness. In practice there is a connection between research and education (or the system of education), both contributing to development of the knowledge of society [23, 24]. Knowledgeable society is able to innovate or continuously improve its procedures, which is necessary for its future.